Integration of Medical Informatics with Other Courses in the Medical Curriculum - Tumstra, C. L. (Methods of Information in Medicine, 1989)
The introduction of a new structure in the Medical Curriculum at the Leiden University Medical School has facilitated the integration of medical informatics subjects with other subjects. The paper describes the holistic nature of the new curriculum, the way Medical Informatics is interwoven with other subjects and the problems which have been encountered.
Keywords: C.A.I.; Curriculum; Educational Assessment; Health Education.